Cognitive Style of File-dependent (FD): Quantitative Reasoning in Generalizing - Muhammad Muzaini; Dwi Juniati; Tatag Y.E Siswono (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Quantitative reasoning is essential in learning and is the primary objective of many educators especially for math teachers worldwide with the aim of how to develop the relationship between mind and the problems of students’ real-life so that it can be solved mathematically. The purpose of this study is to describe the students' quantitative reasoning in generalizing math word problems. The type of this research was descriptive research with a qualitative approach. The subjects of this study were male students enrolled as students of Junior High School in Makassar, and the students had Field-dependent cognitive style. The Group Embedded Figure Test test (GEFT) is used to find subjects that have Field-dependent cognitive style. The main data collection of this study was obtained by using interview technique to investigate the aspect of students' quantitative reasoning ingeneralizing process when completing math problem. The results showed that the subject of male Fielddependent: quantitative reasoning of the subject arises two traits: (1) hooking the relationship of ratios and (2)hooking the proportional relationship, furthermore the subject there is a tendency to see only one quantity change and the subject in finding a new quantity is procedural.